Peran Asam Klorogenat Terhadap Ekspresi Gen; miRNA 146 A, Caspase 3, Cyclin D1, dan Kematian Sel Kanker Hepatoseluler Model Cell Lines Hep-G2 - SUKOHAR, ASEP; HERAWATTI, HENING; WITARTO, ARIEF B (Indonesian Journal of Cancer, 2014)
Chlorogenic acid (CA) is the active compound isolated from medicinal plants, can be used as a chemopreventive agents of hepatocellular cancer (HCC). It works as an exogenous antioxidant and inhibit growth of cancer cells through the inhibition of free radicals. The purpose of this study is to know mechanism of CA in inhibition to growth of Hep-G2 through apoptosis stimulation. In vitro study was performed Hep-G2 cells. The samples were divided into the control group treatment and experiment group expose to 727, 500 and 250 ?M and 3 times repetition. Expression of miRNA 146 A, caspase 3 and cyclin D1 examined by RT-PCR CFX-96. Samples were analysed at 0, 8, 18, and 24 hours after exposure CA. The data were statistically tested by repeated measurement, pearson, and multivariate regression. The results showed that cell death of Hep-G2 were increase as the dose increase and time, at 8 hours after exposure CA cell death of Hep-G2 increased as much as 35,68, 37,75, 40,86%. At 18 hours cell death of Hep-G2 increased as much as 54,56, 56,48, and 59,73%. At 24 hours cell death of Hep-G2 increased as much as 67,73, 69,37, and 72,16%. The lowest expression miRNA 146 A in group 24 hours after exposure at doses of 727 ?M CA (0,85), followed by 500 ?M (1,28) and the highest expression at a dose of 250 ?M (1,61). The result of repeated measurement test: miRNA 146 A and caspase 3 at 8th and 18th hours was significantly different to the 24th with p<0.05. The expression of caspase 3 increase from 0-24 hours, the highest expression of caspase 3 in group 18 hours after exposure at doses CA at 750 ?M (3,86). After 18 hours, expression caspase 3 decreased and the lowest in group 24 hours after exposure: at a dose of 250 ?M (1,52). Expression of cyclin D1 decrease from 0-24 hours with the highest expression at 0 hours (4,35) at a dose of 250 ?M and the lowest expression at 24 hours after exposure to CA (0,32) at a dose of 727 AK ?M.